2019
DOI: 10.1111/aos.14032
|View full text |Cite
|
Sign up to set email alerts
|

Association of chronic hepatitis B virus infection with age‐related macular degeneration

Abstract: PurposeTo study the association between chronic hepatitis B virus (HBV) and age‐related macular degeneration (AMD).MethodsData used in this retrospective, frequency‐matched cohort study were acquired from the Longitudinal Health Insurance Database 2000, which includes medical claims and registration files for 1 000 000 enrolees in the Taiwan National Health Insurance programme. The HBV cohort contained 17 796 patients who received a diagnosis of chronic HBV infection between January 1, 2000 and December 31, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Several studies demonstrated that daily aspirin treatment may be associated with a reduced risk of HBV-related HCC occurrence and recurrence, and liver-related mortality [22,23]. Thus, it is useful to use big data in the analysis HBV infection to establish new findings regarding the association between HBV infection and other diseases [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that daily aspirin treatment may be associated with a reduced risk of HBV-related HCC occurrence and recurrence, and liver-related mortality [22,23]. Thus, it is useful to use big data in the analysis HBV infection to establish new findings regarding the association between HBV infection and other diseases [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Gemmy Cheung et al (2013) reported that an increased body mass index (BMI) and state of hypertension are risk factors for AMD. Moreover, the prevalence of hepatitis‐B is significantly higher in the Korean population compared with other Asian countries (Cho et al 2014; La et al 2014), and hepatitis‐B is by itself a risk factor of AMD (Wu et al 2019). Here, it is pertinent to mention that systemic diseases including DM, hepatitis‐B and increased BMI are also risk factors of periodontal and peri‐implant diseases (Javed et al 2007; Javed et al 2015; Vohra et al 2018; Javed & Romanos 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the incidence of AMD in the study group is also numerically higher than the general incidence of AMD from the same population. [32] Since both SNHL and AMD affect a large percentage of population, a routinely ophthalmic examination can be recommended for patients that diagnosed with SNHL.…”
Section: Discussionmentioning
confidence: 99%